Efl Teachers’ Media In Teaching And Learning Process Under Covid-19 Pandemic Era - Jem, Yosefina Helenora; Raimundus Beda; Yustus Sentus Halum (Jurnal Pendidikan dan Kebudayaan Missio, 2023)
This study is intended to investigate how the EFL teachers in Ruteng run their English class within COVID-19 pandemic era. It focuses on the media used in teaching and learning process and their reason/s of choosing and using those media. It is significance to examine as the teaching and learning process within COVID-19 pandemic is different from conventional teaching and learning process. The study is done under qualitative research and has 30 EFL teachers of both junior and senior high schools in Ruteng, Flores, East Nusa Tenggara, Indonesia as the respondents. The data were collected by using a questionnaire and doing an interview in WhatsApp. The result shows that (1) there are six applications used by EFL teachers as their teaching media (WhatsApp, Google Classroom, Zoom, Google meet and Schoology) with the most dominant application used is WhatsApp. (2) Each EFL teacher in Ruteng uses at least two-four applications in running their online class and (3) the purpose of using those applications are to share the material, arrange task or examination, correct and give feedback to students’ work.